2010
DOI: 10.1590/s1980-65232010000100019
|View full text |Cite
|
Sign up to set email alerts
|

Teaching-learning process in times of the Unified Health System (SUS): training of faculty and dental surgeons in Brazil

Abstract: With the aim of contributing to the current curricular transformation of Brazilian Dentistry courses, this study describes the training of dental surgeons considering the needs of the public Unified Health System (SUS -Sistema Único de Saúde). We focus on the health care model currently in force and emphasize the idea that so as to attain the principles of this model, a shift in the training of instructors who lecture in Dentistry should occur. Some aspects of the training of such instructors, together with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Despite this resistance, concrete advances in the consolidation of SUS as a strategy for the social inclusion of all Brazilians (Vieira, 2009) and interesting experiences in courses are being observed in the health field, along with the adoption of active learning methodologies and better coordination between learning and research with a central focus on the Unified Health System (Diogenes, Souza, Emiliano, & Lima Júnior, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this resistance, concrete advances in the consolidation of SUS as a strategy for the social inclusion of all Brazilians (Vieira, 2009) and interesting experiences in courses are being observed in the health field, along with the adoption of active learning methodologies and better coordination between learning and research with a central focus on the Unified Health System (Diogenes, Souza, Emiliano, & Lima Júnior, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study showed a professional profile which is not compatible with the model of health in force in Brazil, recommended by Family Health [13][14][15][16][17] . The hegemony of the private sector appears to have an influence of the professional practice of the dentists in public service 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The agency of the students of dentistry is the fruit of a satisfactory relationship between them and his professor, and for this, it is important that professors have an adequate qualification so that they present information not only related to the technical-professional education, but broad pedagogical and scientific knowledge based on ethical and humanistic principles [16,17].…”
Section: "Well My Complaint Is This: I Think That All the Basic Subjmentioning
confidence: 99%